Effect of a carbohydrate-electrolyte beverage, lemon tea, or water on rehydration during short-term recovery from exercise - Heung-Sang Wong, S.; Chen, Y. (International Journal of Sport Nutrition and Exercise Metabolism, 2011)
This study examined the rehydration achieved by drinking different beverages during a short-term recovery period (REC) after exercise-induced dehydration. Methods: Thirteen well-trained men (age 22.1 ± 3.3 yr, body mass 61.2 ± 9.1 kg, VO2max 64.9 ± 4.0 ml · kg-1 · min-1, maximum heart rate 198 ± 7 beats/min) ran for 60 min on 3 occasions on a level treadmill at 70% VO2max. All trials were performed in thermoneutral conditions (21 °C, 71% relative humidity) and were separated by at least 7 d. During 4 hr REC, the subjects consumed either a volume of a carbohydrate-electrolyte beverage (CE), lemon tea (LT), or distilled water (DW) equal to 150% of the body weight (BW) lost during the previous run. The fluid was consumed in 6 equal volumes at 30, 60, 90, 120, 150, and 180 min of REC. Results: After the completion of the 60-min run, the subjects lost ~2.0% of their preexercise BW in all trials, and no differences were observed in these BW changes between trials. At the end of REC, the greatest fraction of the retained drink occurred when the CE drink was consumed (CE vs. LT vs. DW: 52% ± 18% vs. 36% ± 15% vs. 30% ± 14%, p < .05). The CE drink also caused the least diuretic effect (CE vs. LT vs. DW: 638 ± 259 vs. 921 ± 323 vs. 915± 210 ml, p < .05) and produced the optimal restoration of plasma volume (CE vs. LT vs. DW: 11.2% ± 2.0% vs. -3.1% ± 1.8% vs. 0.2% ± 2.1%, p < .05). Conclusion: The results of this study suggest that CE drinks are more effective than DW or LT in restoring fluid balance during short-term REC after exercise-induced dehydration.